2018
DOI: 10.1002/jcb.27693
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain attenuates oxidative stress and modulates lipid composition in hippocampus of rats in lipopolysaccharide‐induced hypocampal neuroinflammation in rats

Abstract: Our study aimed to analyze the effect of ouabain (OUA) administration on lipopolysaccharide (LPS)-induced changes in hippocampus of rats. Oxidative parameters were analyzed in Wistar rats after intraperitoneal injection of OUA (1.8 µg/kg), LPS (200 µg/kg), or OUA plus LPS or saline. To reach our goal, activities of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPX), in addition to levels of reduced glutathione (GSH), protein carbonyl (PCO) and lipid peroxidation (LPO) were evaluated. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 49 publications
3
23
0
3
Order By: Relevance
“…To enhance the concentration of circulating ouabain, intraperitoneal injections of ouabain at doses of 1-1.8 µg/kg are widely used [34,39,40]. In this study, rats were treated with ouabain at dose of 1 µg/kg for four days and this experimental protocol was shown doubled serum ouabain level from baseline 0.89 nM to 1.69 nM [34].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…To enhance the concentration of circulating ouabain, intraperitoneal injections of ouabain at doses of 1-1.8 µg/kg are widely used [34,39,40]. In this study, rats were treated with ouabain at dose of 1 µg/kg for four days and this experimental protocol was shown doubled serum ouabain level from baseline 0.89 nM to 1.69 nM [34].…”
Section: Discussionmentioning
confidence: 96%
“…Hindlimb unloading is known to increase oxidative stress [66,67], which may affect the activity of Na,K-ATPase in various cellular systems [68,69], including skeletal muscle [70]. Intraperitoneal injection of ouabain (1.8 µg/kg) is known to attenuate oxidative stress in lipopolysaccharide-induced neuroinflammation in rats [39]. Moreover, ouabain is suggested to play an important role in the control of NF-κB activation [71], where the α2 Na,K-ATPase/NF-κB pathway contributes to neuroinflammatory processes [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies were performed using isolated hippocampus due to its high sensitivity to oxidative stress. Neural tissue has a high rate of oxygen consumption and possesses a high metabolic activity, and therefore, is a tissue more vulnerable to lipid peroxidation as compared to other tissues 32 . Consequently, antioxidant peptides, which rapidly exert their biological functions, have a potential to prevent neuronal damage related to lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%
“…LPS is widely used to induce neuroin ammation [2,3,49,54,62]. Numerous studies showed that LPS treatment could induce central in ammatory response associated with proin ammatory cytokines production, glial cell activation, as well as ROS and RNS generation [2,5,7,40,44,47,54,[63][64][65][66][67][68][69].…”
Section: Discussionmentioning
confidence: 99%